TRANSLATION STUDY OF THREE-WORD LEXICAL BUNDLES IN THE BOOK AT-TAQRIB MATAN ABI SYUJA’ - Muhammad Alfaiz Syahputra; Muhammad Yunus Anis (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
This study aims to describe and analyze the structure, function, translation techniques, methods, and ideology applied in the translation of three-word lexical bundles found in the book At-Taqrib Matan Abi Syuja’ (The Abridged Manual of Islamic Law by Abū Shujāʿ). In addition, this study seeks to reveal how recurring linguistic patterns in classical Arabic religious discourse interact with translation strategies and ideological orientation in the target language. This research is driven by the linguistic uniqueness of Arabic word groups, which differ significantly from those in other languages, such as English and Indonesian, in both their structural formation and communicative function. These differences create considerable challenges for translators, particularly when dealing with religious texts that require high levels of accuracy, consistency, and cultural sensitivity. To address this issue, a descriptive qualitative approach was used, involving data recording and sampling techniques to collect Arabic three-word groups, which were then analyzed using domain, taxonomy, component, and cultural theme analyses. The data were obtained from the chapter on prayer in At-Taqrib, as this section contains a high density of formulaic expressions related to time, procedure, and legal instruction. The findings show that most three-word lexical bundles appear in the form of prepositional phrases that function primarily as markers of location and time in the text. These forms are followed by noun phrases and verb phrases, each contributing specific discourse functions within the legal explanation. These patterns indicate that Arabic lexical bundles not only fulfill syntactic purposes but also play a crucial role in forming text cohesion and conveying contextual meaning. From a translation perspective, translators tend to emphasize the source language through frequent use of literal and semantic translation techniques, with limited application of communicative or idiomatic methods. This preference reflects the translators’ intention to preserve the original meaning, structure, and religious authority of the source text. It reflects an ideology of foreignization that aims to preserve the linguistic and cultural features of the Arabic text while minimizing adaptation to the target language. Such ideological positioning is particularly important in the translation of Islamic legal texts, where deviation from the source may affect theological interpretation. Overall, this study provides insight into the complex relationship between linguistic form, translation strategies, and ideological attitudes. The results show that translators' preference for source-oriented methods contributes to maintaining the sacred tone and authenticity of the text in religious discourse.